Distinct disease trajectories in frontotemporal dementia–motor neuron disease and behavioural variant frontotemporal dementia: A longitudinal study. (18th August 2022) - Long, Zhe; Irish, Muireann; Hodges, John R.; Piguet, Olivier; Burrell, James R.
Abstract: Background and purpose: The heterogeneity of cognitive and behavioural disturbances in frontotemporal dementia–motor neuron disease (FTD‐MND), and clinical differences between FTD‐MND and FTD subtypes, have been illustrated cross‐sectionally. This study aimed to examine the FTD‐MND disease trajectory by comparing clinical features of FTD‐MND and the behavioural variant FTD (bvFTD) longitudinally. Methods: Neuropsychological and disease severity assessments were conducted in a cohort of FTD‐MND (baseline, n  = 42; follow‐up, n  = 18) and bvFTD (baseline, n  = 116; follow‐up, n  = 111) using a longitudinal, case–control design. Age‐, sex‐, and education‐matched controls ( n  = 52) were recruited. Predictors of clinical progression were analyzed. Voxel‐based morphometry analysis was undertaken to investigate the progression of brain atrophy. Results: At baseline, FTD‐MND was characterized by semantic and general cognition deficits, whereas bvFTD had greater behavioural disturbances. General cognition and language deteriorated in FTD‐MND when followed longitudinally. Language deficits at baseline predicted cognitive deterioration and disease progression and correlated with progressive atrophy of language regions. Further deterioration in behaviour was evident in bvFTD over time. The rate of disease progression (i.e., general cognition, semantic association, and disease severity) was significantly faster in FTD‐MND than in bvFTD. Conclusions: FTD‐MND and bvFTD appear to have distinct disease trajectories, with more rapid progression in FTD‐MND. Language impairments should be closely monitored in FTD‐MND as potential predictors of cognitive deterioration and disease progression. Abstract : FTD‐MND and bvFTD have disproportionate impairments in behavioural changes, language disturbances, and general cognition dysfunction at baseline assessments. Deterioration in general cognition and language was prominent as FTD‐MND progressed which was reflected by additional atrophy in brain areas for language production and semantic processing. In contrast, bvFTD was characterised by progressive, but slower, deterioration in general cognition and behaviour. The differed progression pattern between FTD‐MND and bvFTD reinforces the concept that these two entities represent related but distinct clinical syndromes.